2001
DOI: 10.1002/glia.1098
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes of tau protein and mRNA in cultured rat brain oligodendrocytes

Abstract: Oligodendrocytes elaborate an extensive network of multibranched processes and flat membranous sheets. Microtubules (MT) participate in the elaboration and stabilization of myelin-forming processes and are essential for cellular sorting processes. Microtubule-associated proteins (MAPs) are involved in the regulation and stabilization of the dynamic MT network. It has been shown previously that oligodendrocytes express the MAP tau, a phosphoprotein most abundant in neurons of the CNS. In this article, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 53 publications
2
74
0
Order By: Relevance
“…It has been implied that in adult rodent brain only 4R-tau isoforms are expressed. However, our data demonstrated that in rat brain 3R-tau isoforms are present yet at a much lower level (Müller et al, 1997;Gorath et al, 2001), which was later corroborated by Hanes et al (2009). In cultured oligodendrocytes tau protein is developmentally regulated and 4R-isoforms become more prominent, while 3R-isoforms decrease (Seiberlich et al, 2015).…”
Section: Microtubules and The Role Of Tau In Oligodendrocytessupporting
confidence: 58%
See 2 more Smart Citations
“…It has been implied that in adult rodent brain only 4R-tau isoforms are expressed. However, our data demonstrated that in rat brain 3R-tau isoforms are present yet at a much lower level (Müller et al, 1997;Gorath et al, 2001), which was later corroborated by Hanes et al (2009). In cultured oligodendrocytes tau protein is developmentally regulated and 4R-isoforms become more prominent, while 3R-isoforms decrease (Seiberlich et al, 2015).…”
Section: Microtubules and The Role Of Tau In Oligodendrocytessupporting
confidence: 58%
“…In cultured oligodendrocytes derived from the brains of newborn rats all six tau isoforms are present and during in vitro differentiation tau heterogeneity increases while a decrease in phosphorylation is observed (Gorath et al, 2001). It has been implied that in adult rodent brain only 4R-tau isoforms are expressed.…”
Section: Microtubules and The Role Of Tau In Oligodendrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…4), similar to the NSC-Arf6-CKO mice. As it has been reported that tau is expressed in oligodendrocyte lineage cells 11 , we examined whether Cre recombination occurs in oligodendrocytes of the Tau-Cre mice using LacZ reporter mice, but did not observe any such events ( Supplementary Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…In normal neurons, tau associates with microtubules and promotes microtubule stability by suppressing dynamic instability. Tau protein has been implicated in numerous cellular processes, including neurite outgrowth [4,5,19], microtubule transport [11], and oligodendrocyte maturation [13,18]. When hyperphosphorylated, as in AD, tau protein self-aggregates to form NFTs.…”
Section: Introductionmentioning
confidence: 99%